New Refinements of Hermite-Hadamard Inequalities for Quantum Integrals (Journal of Nonlinear Modeling and Analysis, 2026)
In this study, we first introduce two functions including quantum integrals. Then, we prove some properties of these mappings such as convexity and monotony. Moreover, by using the newly defined mappings, we prove some refinements of the left hand side of Hermite-Hadamard inequality for left and right quantum integrals.
Keywords: Convex functions; Hermite-Hadamard inequality; quantum integrals